Enhancing Good Governance through E-Governance: A Comprehensive Study in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
In the context of India's diverse administrative and socioeconomic landscape, this paper examines how electronic governance (e-governance) has revolutionised public service delivery and improved good governance. This study provides a comprehensive examination of e-governance practices in different regions of India by using a descriptive research strategy that combines qualitative and quantitative methods. Its primary goals are to measure the efficiency of service delivery via e-governance, to utilise statistical analysis to identify the connections between e-governance and good governance, and to record the complex stories of people who use and supply e-governance. Results show that e-governance initiatives are associated with better public service delivery, higher citizen satisfaction, and more accountability, transparency, and responsiveness; the study used a stratified sampling method to ensure diverse representation and a sample size of 200 for robust statistical analysis. In addition to providing suggestions for improving the e-governance framework and policies, the results highlight the significant discrepancies between the two in terms of service delivery. This study adds to the ongoing conversation on digital governance by suggesting a way forward for India's governance model that is both digitally inclusive and effective.